Heat exchange simulation of mobile bottle chiller / Rakesh Kamalakannan - Rakesh, Kamalakannan (2019)
The mobile bottle chiller is a conceptual design which makes the consumer to cool down the temperature of drinking fluid without actual refrigerator. This design with its unique ability to cool drinking fluid whenever needed with nominal cost requires the verification of its design specifications to achieve its major objective successfully. The design and simulation of this product involves the concept of heat exchange which is performed by means of a pure mechanical heat transfer mechanism. The major aspects like design specification and material selection are taken in various ratios and compared to establish the best out of others, also such simulation will give the major aspects which has to be considered while designing any system with similar functionalities. Creo parametric 2.0 a designing software and Ansys 16.2 are used to meet the design and simulation the need of this project. The key principle of this mobile bottle chiller is transferring the heat from drinking fluid to the coil and then to the ice cubes in the containers through the conduction process. In this study the major goal is to reduce the temperature of drinking fluid without altering its actual property or nature. Hence the product is designed, and simulation has been conducted to ensure the effective heat transfer by actual implemented concept. Keywords: Heat exchange, Mobile Bottle Chiller, Creo parametric 2.0, Ansys 16.2.